Kaji Eksperimental Rasio Diameter Turbin Angin Propeler Dengan Turbin Angin Venturi Terhadap Performa Turbin Angin Hybrid - Irawan, Ricky; Kurniawan, Iwan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
In this research carried out innovation in wind turbine that generate power using wind energy. Where the propeller wind turbine and the venturi wind turbine are combined into one axis. The purpose of this study was to determine the additional performance of the propeller wind turbine after combining it with the Venturi wind turbine at low wind speeds. The performance of this hybrid wind turbine is measured at each variation in the ratio of the blade diameter of the propeller turbine to the diameter of the venturi turbine. So that the optimal ratio of the ratio of the diameter between propeller wind turbines and venturi wind turbines to this lybrid wind turbine can be obtained. In this study, using three variations of the diameter ratio of the propeller wind turbine, namely 1, 1.2 and 1.4 with the number of 3 blades and the profile of the propeller wind turbine blade using the NREL S833 type. Then add the venturi wind turbine in front of the propeller wind turbine with 3 venturi turbine blades with a diameter of 30 cm. From the test results it is known that the addition of a venturi wind turbine to a small diameter propeller wind turbine has the greatest percentage increase in performance among the three variations of the propeller wind turbine diameter. Keywords: propeller wind turbine, venture wind turbine, hybrid wind turbine